Controlled Surface Adhesion of Macrophages via Patterned Antifouling Polymer Brushes. Issue 1 (24th November 2020) - Striebel, Johannes; Vorobii, Mariia; Kumar, Ravi; Liu, Hui-Yu; Yang, Bingquan; Weishaupt, Carsten; Rodriguez-Emmenegger, Cesar; Fuchs, Harald; Hirtz, Michael; Riehemann, Kristina
Abstract : Macrophages will play an important role in future diagnostics and immunotherapies of cancer. However, this demands to selectively capture and sort different subpopulations, which remains a challenge due to their innate ability to bind to a wide range of interfaces indiscriminately. The main obstacle here is the lack of interfaces combining sufficient antifouling properties with the display of specific binding sites allowing sorting and quantification. Herein, as a proof of principle means, it is introduced to pattern interfaces to locally and selective capture macrophages. The repellent coating is based on antifouling polymer brushes, which can be functionalized. Arrays of binding sites are constructed by microchannel cantilever spotting. Those structures are tested for the isolation of different macrophage subtypes, especially polarized anti‐inflammatory macrophages of the M2 type which can be found associated to tumors ("tumor associated macrophages"; TAMs). Using macrophages as a model system, it is demonstrated that the newly developed surfaces and patterns are efficient for specifically trapping targeted cells and can be useful for further development of therapeutic or diagnostic purposes in the future. Abstract : Antifouling yet reactive surfaces are used for tuning the adhesion of and provide specific binding sites for different subtypes of macrophages. The resulting selective adhesion arrays can become a basis for future applications in macrophage‐based cancer diagnostics and therapies that will strongly rely on the capability to sort and distinguish macrophages of different polarization.